PREGNANT WOMEN'S AUTONOMY AND THE IMPOSITION OF ELECTIVE CESAREAN SECTION IN CHILDBIRTH DECISION-MAKING: AN INTEGRATIVE REVIEW - Oliveira, Agna Freitas de; Cruz, Gerley Adriano Miranda; Jacinto, Everson Izaquiel; Dias, Isadora Morais; Simões, Angélica Lima Brandão (CIPEEX, 2025)
This article aims to examine the autonomy of pregnant women, contrasting it with obstetric violence and the authoritative physician who, as the holder of knowledge, makes all decisions regarding childbirth. The study conducted a thorough analysis of the literature and carried out an integrative review to investigate the relationship between humanized childbirth and the reduction of elective cesareans, focusing on the analysis of four selected articles based on well-established criteria. It was observed that, regardless of the type of childbirth care – whether public or private – good practices reduce the incidence of unnecessary surgical procedures related to childbirth, benefiting both the pregnant woman and the fetus. It became evident, therefore, that the country needs reforms in the obstetric field so that the occurrence of vaginal births that respect the woman's autonomy and physiology surpasses the disproportionately high numbers of cesareans without clinical indication.